Plasticity and adaptation of Ca(2+) signaling and Ca(2+)-dependent exocytosis in SERCA2(+/–) mice - Zhao, Xiao-Song (Oxford University Press, 2001)
Darier’s disease (DD) is a high penetrance, autosomal dominant mutation in the ATP2A2 gene, which encodes the SERCA2 Ca(2+) pump. Here we have used a mouse model of DD, a SERCA2(+/–) mouse, to define the adaptation of Ca(2+) signaling and Ca(2+)-dependent exocytosis to a deletion of one copy of the SERCA2 gene. The [Ca(2+)](i) transient evoked by maximal agonist stimulation was shorter in cells from SERCA2(+/–) mice, due to an up-regulation of specific plasma membrane Ca(2+) pump isoforms. The change in cellular Ca(2+) handling caused ∼50% reduction in [Ca(2+)](i) oscillation frequency. Nonetheless, agonist-stimulated exocytosis was identical in cells from wild-type and SERCA2(+/–) mice. This was due to adaptation in the levels of the Ca(2+) sensors for exocytosis synaptotagmins I and III in cells from SERCA2(+/–) mice. Accordingly, exocytosis was ∼10-fold more sensitive to Ca(2+) in cells from SERCA2(+/–) mice. These findings reveal a remarkable plasticity and adaptability of Ca(2+) signaling and Ca(2+)-dependent cellular functions in vivo, and can explain the normal function of most physiological systems in DD patients.